Performance Analysis of Smart Antenna for Wireless Network - Grover, Gunjan (International Journal of Computer Sciences and Engineering, 2019)
The Smart Antenna are the key solution to enhance the performance of Mobile Communication. It allows energy to be transmitted and received in a particular direction rather than dissipating it in all the directions. Smart antenna System (SAS) combines an antenna array with digital signal processor (DSP) to transmit and receive in adaptive manner. The most important and crucial problem in Smart Antenna is DOA (Direction of Arrival) finding. The performance of Smart Antenna depends upon the resolution of Direction of Arrival. The two classic algorithms for DOA finding is MUSIC (Multiple Signal Classification) and ESPRIT (Estimation of Signal Parameters via Rotational Invariance Technique). However, these two algorithms are unable to work on coherent signals directly as happens in multiple path propagation. For handling such coherent signals both ESPRIT and MUSIC algorithm requires pre-processing method like spatial smoothing which degrades the performance of the Smart Antenna. However, WSF (Weighted Subspace Fitting) is the most superior algorithm which can handle such coherent signals directly without any pre-processing. But this conventional WSF algorithm requires number of signals to be known in advance. The proposed algorithm is the modified WSF which can automatically detect the number of signals and calculate the DOA with better resolution than conventional algorithms like ESPRIT and WSF.